The Use of The Ancient Amaranth (Amaranthus) Grain in Traditional Turkish Cuisine - Merve Onur; Aybuke Ceyhun Sezgin (Turkish Journal of Agriculture: Food Science and Technology)
With its culinary use dating back more than six thousand years, amaranth is known as the ancient grain and the food of the future. Recently recommended for consumption by FAO/WHO, the amaranth plant is a prominent, “forgotten,” functional food that can be used in human nutrition because of its drought-resistant cultivation, gluten-free, and protein and fiber-enriched content. This study evaluates amaranth's botanical character, functional properties, impacts on health, preparation-cooking methods, and use in local and traditional Turkish cuisines. Numerous studies have indicated the association between amaranth’s chemical composition and its anti-oxidative, anti-tumor, gluten-intolerance, and cholesterol-lowering properties, and its assistance with intestinal flora and protein digestibility. Manifold dishes can be made using amaranth seeds and flour in traditional cuisines. Raw and cooked amaranth grains are used in rice, soup, and breakfast cereal. In the food industry, it is a crucial grain alternative to various bakery products, such as bread, pasta, cookies, manti, noodles, biscuits, and crackers, made from amaranth flour. There is a need for alternative recipes to increase the use of amaranth in the kitchen. In this context, it is thought that awareness should be increased by applying it to recipes that can replace semolina and bulgur in traditional cuisines. For this purpose, this study aims to increase the consumption of the ancient grain amaranth by including it in recipes in traditional Turkish cuisine.